(untitled) (Journal of Dhaka National Medical College & Hospital, 2020)
Background: Sudden outbreak of COVID-19 pandemic created panic, anxiety among the population worldwide. The education sector was among many which had taken a strong blow due to pandemic. In the wake of institute shut down, this was a challenging time for professional education which was combated through introduction of e-learning through online classes so as to ensure continuation of teaching-learning process for the medical students. Aims and Objectives: The aim of the study was to rank the effectiveness and satisfaction of online classes compared to classroom conventional teaching among medical students and to evaluate student’s overall perception regarding online learning. Materials and Methods: This study has been designed to get opinion from 4th year MBBS medical students of Shaheed Monsur Ali Medical College, Dhaka regarding the perception on online learning during COVID -19 pandemic. In this survey, total 103 medical students of 4th year took part. This online survey was carried out from 2nd August, 2021 to 10th August, 2021,after completion of 12 weeks of online classes. A set of self designed questionnaire based on 5-point Likert scale was given to the students, to rank the effectiveness of online learning and their understanding with the satisfaction level on various parameters. The remaining items in the questionnaire comprised a mixture of question styles. All the students voluntarily participated in the survey. Results: The study result shows that in 2 parameters, students rated the online-classes to be equally effective, the parameters which are contributing to offering convenience and meeting individual learning needs. In other 2 parameters, regarding building skills and knowledge, offering better understanding through recorded classes the students found it to be somewhat more effective. But regarding interaction level, contributing to effective communication and balancing of practical and theoretical knowledge, the students found it to be somewhat less effective. We could come to an interpretation that students were not much satisfied with this way of teaching but definitely it was the need of the hour. Most of the students had positive perception towards online classes. Conclusion: We could conclude from our study that online education can supplement the process of present education system, but it cannot be a substitute for the established system of education. J. Dhaka National Med. Coll. Hos. 2020; 26 (02): 15-19